Ligand effect of two Dy(III) complexes on single-molecule magnetism. (1st July 2020) - Wang, Xia; Wang, Ling-Yun; Wu, Su-Yun; Ou, Li-Juan; Yang, Guo-Ping
Graphical abstract: Two different Dy(III) complexes which act as SSMs have been synthesized by regulating the N, O chelating ligands. Comparing the two SMMs, because there is an additional oxygen coordination site on the ligand in the structure of complex 2 to coordinate with Dy(III) ions, this leads to the structure going from the binuclear for complex 1 to trinuclear for complex 2, resulting in a huge difference in the ac magnetic susceptibilities between the two complexes. Abstract: The organic ligands ( E )-3-(pyridin-2-ylmethyleneamino)propane-1, 2-diol (H2 L1 ) and ( E )-2-((2, 3-dihydroxypropylimino)methyl)quinolin-8-ol (H3 L2 ) were reacted with Dy(NO3 )3 ·6H2 O at 80 °C to obtain the binuclear complex [Dy2 (HL1 )2 (NO3 )4 ] (1 ) and the trinuclear complex [Dy3 (HL2 )3 (OH)(H2 O)(CH3 OH)2 ](NO3 )2 ·CH3 CN (2 ), where the H2 L1 and H3 L2 ligands were obtained from picolinaldehyde or 8-hydroxyquinoline-2-carbaldehyde and 3-aminopropane-1, 2-diol by an in-situ reaction. Magnetic investigations showed that complex 1 exhibited field-induced single-molecule magnetic behavior with an energy barrier of 4.65(6) K under a 1200 Oe field. By contrast, complex 2 was a clear single-molecule magnet, with energy barriers of 7.7(2) and 25.2 (3) K under different dc-fields.